PENGEMBANGAN KEWIRAUSAHAAN DI SMAN 1 MUARA PADANG - Handayani, Esti; Marpudhok, Marpudhok (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The issues examined are: 1) How development of entrepreneurialbusiness unit in SMAN 1 Muara Padang? 2) How entrepreneurialproduction units in SMAN 1 Muara Padang?The research subjects are headmaster, chairman of the committee andteachers. Using ethnographic research approach. Method of data collection using indepth interviews, observation and documentation. Technique of data analysis using triangular. Results of the study are: 1) the development of entrepreneurial business unit in SMAN 1 Muara Padang is still limited to the school cooperative effort is still limited to fulfilling the needs of students such as stationery and books, haven't touched the needs of all the citizens of the school; 2) Development of entrepreneurial production units in SMAN 1 Muara Padang is still limited to the activities of the tailoring school uniform and still involves a seamstress from outside power, has not been fully resolved by the school's own citizens. Whereas the development of production units in the form of maximize the potential of citizen schools in serving the tailoring school uniform and other service uniforms, as well as utilizing landfill covering an area of 4,000 m2 belonging to the school utilized into three parts, covering an area of 2,000 m2 can be used for crops of fruit, such as mango 10750 m2 for plant vegetable soup, and a 1,000 m2 for plant chemist shop alive.